Electrical and Myocardial Remodeling in Primary Aldosteronism - Curione, Mario; Petramala, Luigi; Savoriti, Claudio; Verrenti, Marisa; Baiocco, Erika; Salvatore, Stephanie; Zinnamosca, Laura; Iannucci, Gino; Sciomer, Susanna; Letizia, Claudio (Frontiers in Cardiovascular Medicine, 2014)
Objective and design: primary aldosteronism (PA) represents the most common cause of secondary hypertension. An higher risk of cardiovascular events has been reported in patients with PA than otherwise similar patients with essential hypertension (EH). At today few studies has been investigated the electrocardiographic changes in PA patients compared to EH patients. Methods: to investigate the electrocardiographic changes and heart remodeling in PA we enrolled 61 consecutive patients, 30 with PA (12 with aldosterone producing adenoma-APA and 18 with bilateral adrenal hyperplasia-IHA) and 30 with EH. In all subjects electrelectrocardiographic parameters were evaluated from 12-lead electrocardiograms and heart remodeling with echocardiogram. Results: no significant differences in age, sex , body mass index (BMI) and blood pressure were found in two groups. The P wave and PR interval duration were significantly prolonged in patientswith PA respect to EH (p< 0.003 and p< 0.002, respectively). First degree atrioventricular block was present in 16% patient with PA and only in 3.2% patients with EH. In PA patients the interventricular septum thickness (IVST) correlated with left ventricular mass indecized (LVMi) (r= 0.54; p< 0.04), and with PR duration (r= 0.51; p< 0.03). Left ventricular hypertrophy (LVH) was present in 53% patients with PA and in 26% patients with EH (χ2 p<0.03). Conclusions: in this case-control study, patients with PA show more anatomic and electrical heart remodeling than those with EH. We hypothesize that in patients with PA these cardiac changes may play a role for the increased risk of future cardiovascular events.